Soluble and insoluble dipeptide repeat protein measurements in C9orf72-frontotemporal dementia brains show regional differential solubility and correlation of poly-GR with clinical severity - Annelies Quaegebeur (Acta Neuropathologica Communications, 2020)
Abstract A C9orf72 repeat expansion is the most common genetic cause of frontotemporal dementia (FTD) and amyotrophic lateral sclerosis. One of the suggested pathomechanisms is toxicity from dipeptide repeat proteins (DPRs), which are generated via unconventional translation of sense and antisense repeat transcripts with poly-GA, poly-GP and poly-GR being the most abundant dipeptide proteins. Animal and cellular studies highlight a neurotoxic role of poly-GR and poly-PR and to a lesser degree of poly-GA. Human post-mortem studies in contrast have been much less clear on a potential role of DPR toxicity but have largely focused on immunohistochemical methods to detect aggregated DPR inclusions. This study uses protein fractionation and sensitive immunoassays to quantify not only insoluble but also soluble poly-GA, poly-GP and poly-GR concentrations in brain homogenates of FTD patients with C9orf72 mutation across four brain regions. We show that soluble DPRs are less abundant in clinically affected areas (i.e. frontal and temporal cortices). In contrast, the cerebellum not only shows the largest DPR load but also the highest relative DPR solubility. Finally, poly-GR levels and poly-GP solubility correlate with clinical severity. These findings provide the first cross-comparison of soluble and insoluble forms of all sense DPRs and shed light on the distribution and role of soluble DPRs in the etiopathogenesis of human C9orf72-FTD.